METODE PEMBELAJARAN KOPERATIF UNTUK KESIAPAN BELAJAR MATEMATIKA SISWA MTS - Khotimah, Nurrul; Adi Heryadi, Adi (JURNAL PSIKOLOGI INSIGHT, 2019)
This study aimed to prove cooperative learning in improving mathematics learning readiness of Islamic junior high school (MTs) students. This research was an experimental study with 50 partisipants that devided randomly in two groups, experiment and control. The design of the experiment was a pretest-posttest control group. The experiment was engeged in cooperative learning in mathematics subject and the control group only learned mathematic subject in traditional methods. The instrument was students' readiness questionaire with reliability coefficient of 0.913. The results showed that cooperative learning methods improved the mathematics learning readiness of Islamic Junior High School students. Mathematics learning readiness is important to improved before the students learn mathematics in class.